Socio-economic Determinants of Adoption of Maize Production Technologies among Smallholders - Godfrey Onuwa; S.S. Mailumo; S.O. Oyewole (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2023)
Agricultural technology adoption is germane for improved farm efficiency and productivity. Thus, the socioeconomic determinants of adoption of maize production technologies among smallholders were analyzed. Primary data collected via multi-stage sampling from 101 respondents was empirically evaluated using descriptive statistics and Logit regression. The respondent’s socioeconomic factors affected maize production technology adoption. Several maize production technologies were available in the study area; however adoption of these technologies among respondents was relatively low. The coefficient of multiple determination (R2) was 0.74827. The regression coefficients of household size (0.541), education (0.331), farm experience (0.615), farm size (0.448) and extension contact (0.457) were statistically significant at p0.05 probability level. Furthermore, the constraints identified by respondents also affected the adoption of maize production technologies in the study area. This study recommends subsidizing technology cost, improved cooperative activities; access to technology, credit and extension services, farm labour supply and tenure policy modifications.